2007
DOI: 10.1103/physrevd.76.074020
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic nucleon form factors in instant and point form

Abstract: We present a study of the electromagnetic structure of the nucleons with constituent quark models in the framework of relativistic quantum mechanics. In particular, we address the construction of spectator-model currents in the instant and point forms. Corresponding results for the elastic nucleon electromagnetic form factors as well as charge radii and magnetic moments are presented. We also compare results obtained by different realistic nucleon wave functions stemming from alternative constituent quark mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 82 publications
6
32
0
Order By: Relevance
“…Here ρ is the probability density associated with an intermediate spectator state of invariant 7 It appears that this class includes the model of (Glozman et al, 1998) if a point-form spectator model (PFSM) is employed for the electromagnetic current operator (Melde et al, 2007). Of the currents considered in this connection, only the PFSM can produce results in fair agreement with experiment.…”
Section: Pion Cloudsupporting
confidence: 64%
“…Here ρ is the probability density associated with an intermediate spectator state of invariant 7 It appears that this class includes the model of (Glozman et al, 1998) if a point-form spectator model (PFSM) is employed for the electromagnetic current operator (Melde et al, 2007). Of the currents considered in this connection, only the PFSM can produce results in fair agreement with experiment.…”
Section: Pion Cloudsupporting
confidence: 64%
“…An ambiguity in defining such a spectator current, however, enters through a normalization factor N that has to be introduced in order to recover the hadron charge from the electric form factor in the limit Q 2 → 0 [30]. Because both quantities,Q and N depend effectively on all quark momenta and not only on those of the active ones, the model current constructed in this way cannot be considered as a pure one-body current [31]. It has therefore been termed "point-form spectator model" (PFSM) to distinguish it from the usual impulse approximation.…”
Section: B Comparison With the Point-form Spectator Modelmentioning
confidence: 99%
“…These differences resemble the situation for the electromagnetic nucleon form factors. In the latter case the stronger falloff produced by the PFSM is a welcome feature that brings the theoretical predictions from constituent quark models close to experiments [31]. For the usual frontform spectator current in the q + = 0 frame agreement with experiment is achieved only by introducing electromagnetic form factors for the constituent quarks [33].…”
Section: B Comparison With the Point-form Spectator Modelmentioning
confidence: 99%
“…The effective one-gluon exchange interaction [1,2,3,4] was replaced by one-boson exchange interactions between constituent quarks [6] or by instanton-induced interactions [5]. The improved baryon wave functions provided the basis for calculations of partial decay widths [7,8,9,10,11], of helicity amplitudes [12,13], and of form factors [14,15,16,17]. The spectrum of nucleon and ∆ resonances calculated on the lattice [18] shows striking agreement with expectations based on quark models: with increasing mass, there are alternating clusters of states with positive and with negative parity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the transition from constituent quarks to current quarks can be followed by precise measurements of the masses of excited hadron resonances [30]. The splitting in (squared) mass between two states forming a parity doublet (like ∆(1950) F 17 and ∆(2200)G 17 , 1.04 GeV 2 ) is slightly smaller than the mean mass square difference per unit of angular momentum (the string tension, 1.1 GeV 2 ). This effect can possibly be interpreted as weak attraction between parity partners in the 2 GeV mass region and as onset of a regime in which chiral symmetry is restored [31].…”
Section: Introductionmentioning
confidence: 99%